2004
DOI: 10.1242/jcs.01404
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localisation of the G-actin sequestering peptide thymosin β4

Abstract: Thymosin β4 is regarded as the main G-actin sequestering peptide in the cytoplasm of mammalian cells. It is also thought to be involved in cellular events like cancerogenesis, apoptosis, angiogenesis, blood coagulation and wound healing. Thymosin β4 has been previously reported to localise intracellularly to the cytoplasm as detected by immunofluorescence. It can be selectively labelled at two of its glutamine-residues with fluorescent Oregon Green cadaverine using transglutaminase; however, this labelling doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 69 publications
4
88
0
Order By: Relevance
“…For example, it has been reported that phosphoinositide, which is known to stimulate polymerization, is found in the nucleus, and phosphoinositide signaling is initiated by a nucleus-specific isoform of phospholipase C (53,54). Several other actin-binding proteins, including cofilin, thymosin b4, gelsolin, and CapG, have also been observed in the nucleus (55)(56)(57)(58)(59)(60). These proteins function to decrease actin polymerization and/or regulate the size of actin polymers through their severing and capping activities (41,(55)(56)(57)(58)(59)(60), thus antagonizing the stimulatory functions of N-WASP and the Arp2/3 complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that phosphoinositide, which is known to stimulate polymerization, is found in the nucleus, and phosphoinositide signaling is initiated by a nucleus-specific isoform of phospholipase C (53,54). Several other actin-binding proteins, including cofilin, thymosin b4, gelsolin, and CapG, have also been observed in the nucleus (55)(56)(57)(58)(59)(60). These proteins function to decrease actin polymerization and/or regulate the size of actin polymers through their severing and capping activities (41,(55)(56)(57)(58)(59)(60), thus antagonizing the stimulatory functions of N-WASP and the Arp2/3 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Several other actin-binding proteins, including cofilin, thymosin b4, gelsolin, and CapG, have also been observed in the nucleus (55)(56)(57)(58)(59)(60). These proteins function to decrease actin polymerization and/or regulate the size of actin polymers through their severing and capping activities (41,(55)(56)(57)(58)(59)(60), thus antagonizing the stimulatory functions of N-WASP and the Arp2/3 complex. Therefore, the regulation of nuclear actin is likely to involve both mechanisms that stimulate polymerization and depolymerization as well as those that control the size of actin filaments.…”
Section: Discussionmentioning
confidence: 99%
“…The protein profile obtained aftermanual curation of the data (Supplementary Figure 1), and in particular Table 1, explains the ability of H6O5 cells to form solid tumors when grafted onto mice (Figure 1d). In brief, H6O5 cells were found to overexpress Thymosin beta 4, an actin-binding protein previously described as having a role in angiogenesis [34,35], while having low protein levels of thrombospondin 1, an angiogenesis inhibitor, that binds to proteins on the cell surface, thereby modulating cell motility and cell adhesion events [36,37].…”
Section: Functional Classification Of the Proteins Identifiedmentioning
confidence: 99%
“…SRF is co-activated by myocardin 15 or MRTFs A and B 16 . These SRF coactivators are interacting with G-actin and translocate to the nucleus 17 , when G-actin levels decrease, for example, due to sequestration by the G-actinbinding peptide thymosin 4 (T 4) [18][19][20] . Since T 4 is a potent pro-angiogenic factor 21 , an involvement of the T 4-MRTF-SRF axis in vascular growth would require transcriptional activation beyond well-known myogenic proteins 13,14 .…”
mentioning
confidence: 99%